The Impact of Positive Fluid Balance on Sepsis Subtypes: A Causal Inference Study - Sharad Patel; Adam Green; Yanika Wolfe; Gregory Felock; Samantha Epstein; Nitin Puri (Critical Care Research and Practice)
Introduction. Sepsis, the leading cause of death in hospitalized patients globally, was investigated in this study, examining the varying effects of positive fluid balance on sepsis subtypes through causal inference. Methods. In this study, data from the eICU database were utilized, extracting 35 features from sepsis patients. Fluid balance during ICU stay was the treatment, and ICU mortality was the primary outcome. Data preprocessing ensured linear assumptions for logistic regression. Binarized positive fluid balance with mortality was examined using DoWhy’s logistic regression, while continuous data were analyzed with random forest T-learner. ATE served as the primary metric. Results. Results revealed that septic patients with higher fluid balance had worse mortality outcomes, with an ATE of 0.042 (95% CI: (0.034, 0.047)) using logistic regression and an ATE of 0.0340 (95% CI: (0.028–0.040)) using T-learner. In the pulmonary sepsis subtype, higher mortality was associated with increased fluid balance, showing an ATE of 0.047 (95% CI: (0.037, 0.055)) using logistic regression and an ATE of 0.28 (95% CI: (0.22, 0.34)) with T-learner. Conversely, urinary sepsis patients had improved mortality with higher fluid balance, presenting an ATE of −0.135 (95% CI: (−0.024, −0.0035)) using logistic regression and an ATE of −0.28 (95% CI: (−0.34, −0.22)) with T-learner. Conclusion. Our research implies that fluid balance impact on ICU mortality differs among sepsis subtypes. Positive fluid balance raises mortality in sepsis and pulmonary sepsis but may protect against urinary sepsis. Further trials are needed to confirm these findings.